Analisis Potensi Kulit Jagung sebagai Media Adsorben terhadap Limbah Minyak dan Lemak - Wati, Fitra; Wibowo, Dwiprayogo; Rosdiana, Rosdiana; Ilham, Ilham (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2024)
This study investigates the possibility of using corn husk as an adsorbent media to reduce fat and oil levels in wastewater from restaurants. Restaurant activities produce wastewater containing oil and fat from cooking and food processing activities that require treatment before being discharged directly into the environment, including oil and fat parameters. The purpose of the study was to analyze the ability of corn husk to absorb restaurant wastewater contaminants. Adsorption is the approach used in this study. Corn husk is one type of adsorbent used. Corn husk contains 44.08% cellulose which allows corn husk to act as an adsorbent. The adsorption process was carried out using variations in contact time and adsorbent weight. The oil and fat content was analyzed using the gavimetric extraction method. The results showed that the best oil and fat removal capacity was obtained at a contact time of 80 minutes with an adsorbent weight of 12.091 g at 5.58 mg/L with an absorption efficiency of 8.82%. The findings of this study are expected to encourage more research in this field, such as increasing adsorption efficiency, developing other adsorption technologies based on agricultural waste, or adsorption applications in other fields such as wastewater treatment and environmental remediation.